2012
DOI: 10.3797/scipharm.1208-02
|View full text |Cite
|
Sign up to set email alerts
|

Transfersomes: A Novel Vesicular Carrier for Enhanced Transdermal Delivery of Sertraline: Development, Characterization, and Performance Evaluation

Abstract: The aim of the present study was to investigate transfersomes as a transdermal delivery system for the poorly soluble drug, sertraline, in order to overcome the troubles associated with its oral delivery. Different transfersomal formulations were prepared with non-ionic surfactant (span 80), soya lecithin, and carbopol 940 by the rotary evaporation sonication method. The prepared formulations were characterized for light microscopy, particle size analysis, drug entrapment, turbidity, drug content, rheological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 156 publications
(98 citation statements)
references
References 20 publications
5
92
0
1
Order By: Relevance
“…It was reported that at high surfactant concentration, the drug release was low due to formation of rigid micelles [45]. These findings were agreed with Shaji et al [48] and Gupta et al [29], who reported that drug release was related to EE and drug loading. In the present study the optimum surfactant concentration for drug release was found to be achieved by using 5 mg tween 80.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…It was reported that at high surfactant concentration, the drug release was low due to formation of rigid micelles [45]. These findings were agreed with Shaji et al [48] and Gupta et al [29], who reported that drug release was related to EE and drug loading. In the present study the optimum surfactant concentration for drug release was found to be achieved by using 5 mg tween 80.…”
Section: Discussionsupporting
confidence: 83%
“…In the present study the optimum surfactant concentration for drug release was found to be achieved by using 5 mg tween 80. This finding is also agreed with Gupta et al [29], and Kaylani et al [49], who found that the use of tween 80 as a non-ionic surfactant significantly increased (p<.0.05) drug release from the transfersomal suspensions compared with SDC as an ionic surfactant. The possible explanation of the enhancing effect of tween 80 on drug release rate was the large volume of hydrophilic head group consisting of several polyethylene chains [50].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, these bilayer and acyl‐chain lipid products have not fulfilled their practical potential due to their insufficient morphological stability and inclusion leakage in vitro and in vivo 9. To address these drawbacks, various optimizations have been approached,10 which include surface coating with certain amphiphilic molecules (PEGylation; where PEG is polyethylene glycol) and cholesterols for prolonging circulation,11 enhancing elasticity using transferosome formulations for transdermal delivery,12 and improving bioavailability that employ drug–lipid conjugates 13. Although these strategies have significantly promoted the therapeutic potential of traditional lipid nanoparticles with increasingly broad applications, several concerns such as insufficient coverage of surface coating on phospholipid bilayers,14 and the morphological stability of lipid assemblies are likely to decrease after modulating composition, charge, and bilayer architecture.…”
Section: Introductionmentioning
confidence: 99%